Acoustic monitoring to document the spatial distribution and hotspots of blast fishing in Tanzania. Issue 1 (15th December 2017) - Braulik, Gill; Wittich, Anja; Macaulay, Jamie; Kasuga, Magreth; Gordon, Jonathan; Davenport, Tim R.B.; Gillespie, Douglas
Abstract: Destructive fishing using explosives occurs in a number of countries worldwide, negatively impacting coral reefs and fisheries on which millions of people rely. Documenting, quantifying and combating the problem has proved problematic. In March–April 2015 231 h of acoustic data were collected over 2692 km of systematically laid transects along the entire coast of Tanzania. A total of 318 blasts were confirmed using a combination of manual and supervised semi-autonomous detection. Blasts were detected along the entire coastline, but almost 62% were within 80 km of Dar es Salaam, where blast frequency reached almost 10 blasts/h. This study is one of the first to use acoustic monitoring to provide a spatial assessment of the intensity of blast fishing. This can be a useful tool that can provide reliable data to define hotspots where the activity is concentrated and determine where enforcement should be focused for maximum impact. Highlights: Quantifying and monitoring fishing with explosives is challenging. Acoustic data were collected over 2692 km of systematic transects in Tanzania. 318 blasts were confirmed, almost 62% within 80 km of Dar es Salaam. Blast frequency reached almost 10 blasts/h. Acoustic monitoring can identify blasting hotspots and allow targeted enforcement.